Release of Plasmodium sporozoites requires proteins with histone-fold dimerization domains - Chiara Currà (Nature Portfolio, 2016)
Oocyst rupture and release of malaria sporozoites is needed for transmission of parasites from vector to humans. Here the authors identify two proteins, which they name ORP1 and ORP2, that form heterodimers and are required for oocyst rupture.